Dynamic growth changes in fetal growth restriction using serial ultrasonographic biometry and umbilical artery doppler: The multicenter PORTO study. Issue 1 (29th September 2022) - Cody, Fiona; Unterscheider, Julia; Daly, Sean; Geary, Michael; Kennelly, Mairead; McAuliffe, Fionnuala; Morrison, John; O'Donoghue, Keelin; Hunter, Alyson; Dicker, Patrick; Tully, Elizabeth; Fhearaigh, Rachel; et al.
Abstract: Objective: To describe the growth dynamics of fetuses with initial fetal growth restriction (FGR) later outgrowing the 10th centile for estimated fetal weight with respect to perinatal outcomes and maternal factors. Methods: A multicenter prospective study recruited 1116 patients for ultrasound surveillance between 2010 and 2012. All pregnancies were growth‐restricted singleton gestations between 24 + 0 and 36 + 0 weeks. Biometry and Doppler analysis were carried out, and delivery and adverse perinatal outcomes were recorded. Results: A total of 193 (17%) fetuses outgrew their diagnosis of initial FGR (surpassed the 10th centile) on their last sonogram before delivery. These fetuses were termed "growers, " to compare with the true FGR group. The mothers of "growers" were less likely to be smokers (14% vs 25%, P  = 0.0001) or affected by hypertensive pregnancy complications (5.2% vs 15%, P  = 0.001). Of the growers, 49 (25%) had an abnormal umbilical artery Doppler; however, in most cases (33/49, 67%), this was a single episode of raised umbilical artery pulsatility index, which subsequently normalized. Conclusion: There were dynamic growth changes in FGR fetuses, with 17% outgrowing their original diagnosis. Positive growth spurts more commonly occurred in healthy mothers. Once a fetus had outgrown the 10th centile, antenatal surveillance could be decreased. Synopsis: There are dynamic growth changes in fetuses with growth restriction, with recovery from growth restriction occurring most commonly in healthy mothers.